2006
DOI: 10.1016/j.molcata.2005.09.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of M ion oxidation state in Sr1−xMxTiO3±δ perovskites in methane catalytic flameless combustion

Abstract: Sr 1−x M x TiO 3±δ (x = 0 or 0.1; M = K or Gd) have been compared as catalysts for the flameless combustion of methane. The samples were prepared both by traditional sol-gel (SG) and by flame-hydrolysis (FH) procedure. All the catalysts possessed the perovskite-like structure, with some SrCO 3 as impurity with Sr 0.9 K 0.1 TiO 3±δ prepared by SG procedure. All the samples prepared by FH were better catalysts than those prepared by SG. A further improvement in the catalytic activity was obtained with M = K, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
(32 reference statements)
1
6
0
Order By: Relevance
“…(a) Steady-state conversions obtained for the oxidation reaction of CH 4 over LSTO systems consolidated at different conditions. (b) CH 4 oxidation reaction rates of LSTO systems presented in this work compared with reported values by Oliva et al for donor-doped SrTiO 3 (Sr 0.9 Gd 0.1 TiO 3 ) sintered in oxidizing conditions 75. The values are retrieved at T = 550 °C and normalized by surface area.…”
mentioning
confidence: 81%
“…(a) Steady-state conversions obtained for the oxidation reaction of CH 4 over LSTO systems consolidated at different conditions. (b) CH 4 oxidation reaction rates of LSTO systems presented in this work compared with reported values by Oliva et al for donor-doped SrTiO 3 (Sr 0.9 Gd 0.1 TiO 3 ) sintered in oxidizing conditions 75. The values are retrieved at T = 550 °C and normalized by surface area.…”
mentioning
confidence: 81%
“…Double perovskites associating Ni and Cu were prepared by Hu et al, who showed that the activity of La 2 CuNiO 6 for methane oxidation was much higher than that of the single perovskite (LaNiO 3 ) while the physical mixture LaNiO 3 + LaCuO 3 was less active than LaNiO 3 at isospace velocity. Chromites were also investigated by Kaddouri et al, while titanates were studied by the group of Forni and by Popescu et al , ESR characterization showed the presence of different oxygen species associated to Ti cations, O 3 – /Ti 4+ species having a crucial role in oxidation reactions. Silver seems to be a good substitute for Sr in SrTiO 3 titanates.…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…The high temperature required to dry out and combust the droplets is reached with a torch, which is usually fed with oxygen or air as oxidizing agent while the fuels are methane or hydrogen [77][78][79][80][81] in the flame hydrolysis asset. By contrast, in the flame spray pyrolysis version of the technique, the fuel is constituted by the organic solvent used to dissolve the precursors of the oxide.…”
Section: Ii161 Flame Spray Pyrolysis and Hydrolysismentioning
confidence: 99%